Can ingroup love harm the ingroup? Collective narcissism and objectification of ingroup members. (October 2022) - Cichocka, Aleksandra; Cislak, Aleksandra; Gronfeldt, Bjarki; Wojcik, Adrian Dominik
We examined how collective narcissism (a belief in ingroup greatness that is underappreciated by others) versus ingroup identification predicts treatment of ingroup members. Ingroup identification should be associated with favorable treatment of ingroup members. Collective narcissism, however, is more likely to predict using ingroup members for personal gain. In organizations, collective narcissism predicted promoting one's own (vs. group) goals (prestudy: N = 179), and treating coworkers instrumentally (Study 1: N = 181; and longitudinal Study 2: N = 557). In Study 3 ( N = 214, partisan context), the link between collective narcissism and instrumental treatment of ingroup members was mediated by self-serving motives. In the experimental Study 4 ( N = 579, workplace teams), the effect of collective narcissism on instrumental treatment was stronger when the target was an ingroup (vs. outgroup) member. Across all studies, ingroup identification was negatively, or nonsignificantly, associated with instrumental treatment. Results suggest that not all forms of ingroup identity might be beneficial for ingroup members.